Dampak UU Akuntan Publik Terhadap Perkembangan Profesi, Pendidikan Akuntansi Dan Gelar CPA Di Indonesia - Eva Ulfah Rahayu (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2014)
The birth of UU No. 5 Tahun 2011 has been a legal framework to facilitate and accommodate the interests of the profession of Certified Public Accountants. But among the many positive impacts generated, this Actual so still giving concern to the development of Public Accounting profession in Indonesia. It is still a matter of controversy among practitioners of economics, especially those engaged in the profession of Certified Public Accountants.